A Comparative Analysis of ADRs under Obeticholic Acid and Ursodeoxycholic Acid in Cholestatic Liver Diseases Using the FAERS Database - Zhu, Meng; Tao, Linghui; Zhu, Feiye; Zhang, Yongsheng (Drug Research, 2024)
Background The objective of this study was to compare the safety profiles of OCA and UDCA for the treatment of PBC using the FDA Adverse Event Reporting System database.Methods We extracted reports for OCA from 2016 to 2023 and UDCA from 2004 to 2023. Demographic details, adverse events (AEs), and concomitant medications were analyzed using descriptive statistics and signal detection methods.Results The most common for OCA were pruritus (1345 cases, ROR 20.96) and fatigue (528 cases, ROR 3.46). UDCA was more frequently associated with hepatocellular carcinoma (22 cases, ROR 16.37) and type I hypersensitivity reactions (11 cases, ROR 12.77). OCA was also linked to a higher frequency of constipation (161 cases, ROR 3.92) and increased blood alkaline phosphatase levels (145 cases, ROR 44.27).Conclusion This study reveals distinct safety profiles for OCA and UDCA in the treatment of PBC. OCA is associated with a higher frequency of pruritus, fatigue, constipation, and increased blood alkaline phosphatase levels, while UDCA is linked to hepatocellular carcinoma and type I hypersensitivity reactions. These findings support personalized treatment approaches based on individual patient characteristics.
Keywords: obeticholic acid; ursodeoxycholic acid; adverse events; FAERS